Math anxiety and science anxiety are associated with spatial cognition and STEM interest in deaf, hard of hearing, and hearing people - Rachel Gabriella Pizzie; Rachel Marie Sortino; Christina Eun-Young Kim; Rachel Inghram (npj Science of Learning)
Abstract Many students in STEM experience decreased performance due to anxiety, namely math and science anxiety. However, spatial skills are correlated with better STEM outcomes. Our research addressed a previous gap in the literature, investigating if STEM anxiety or spatial experiences have a stronger relationship with STEM outcomes. In this online study, we explored which factors were related to STEM outcomes in a sample of deaf, hard of hearing (DHH), and hearing adults (N = 115) who had experience with American Sign Language, which has been associated with improved spatial skills. Participants completed a mental rotation task, and self-reported interest in STEM, and anxiety. Results showed math and science anxiety were significant predictors of mental rotation performance and interest in studying STEM, even when accounting for other spatial factors. For DHH and hearing people alike, math and science anxiety are important factors that must be addressed to encourage STEM success.